Agrifood trade - Diao, Xinshen; Masias, Ian; Lwin, Wuit Yi (International Food Policy Research Institute, 2024)
Agrifood exports make up about one-third of Myanmar’s total exports, and their share of both total exports and as a ratio of total GDP has risen in recent years. Agrifood exports have the potential to generate higher income for farmers, traders, processors, and other stakeholders within agrifood value chains. Additionally, they can contribute to the country’s foreign exchange earnings, supporting the importation of manufactured products embedded with modern technology required for the transformation of the agrifood sector. This chapter analyzes the past performance of key agrifood exports and assesses their potential role in the transformation of Myanmar’s agrifood system and the overall economy.